Practices of Islamic Ethics in the Electronics Industry in Bangladesh: A Study on Minister Hi-Tech Park Electronics Ltd. - Khan, M.A Razzak; Latif, Wasib Bin; Ahmed, Selim; Hira, Marzan Ara; Tanu, Dil Ruba (International Journal of Islamic Business & Management, 2019)
The main purpose of this paper is to identify the practices of Islamic ethics at Minister Hi-Tech Park Electronics Ltd. on the basis of focus group discussion. Islam places the most emphasis on ethical values in all aspects of human life especially in business. By running the business Islamic point of view Minister Hi-Tech Park Electronics Ltd. is attaining competitive advantage. There have been three focus group of discussion; the first one is with the internal employees of the company (top management to field level employee, the second one is with the board of Shariah and stakeholders of the company (investors, suppliers, creditors, competitors) and the third one is with the income and tax revenue board of Bangladesh. The paper has also presented the various repeatedly verses from Quran and the teachings of the prophet. The three focus groups discussed on the basis of Quran, Hadith and the variables like “Islam as entire course of life”, “Morality of individuals, Superiority of business concept, “Integrated business ethics”, Racism, Mutual consent, Halal Items practice of Minister Hi-Tech Park Ltd. Being Muslims, we have to follow the rules and regulation of Islamic ethics which stated by Islamic jurisprudence. Minister Hi-Tech Park Ltd. will sustain its image and will be able to survive.